The Effect of Market Power and Systematic Risk on Future Earnings Response Coefficient with Tax Compliance as a Moderation - Didit Santoso; Muhammad Nuryatno (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to analyze the influence of market power and systematic risk on the future earnings response coefficient (ERC), with tax compliance as a moderating factor. In this context, the study will examine how market power and systematic risk affect market reactions to future earnings, considering the role of tax compliance as a moderating factor. Relevant references for this study include factor analysis that influences ERC in financial sector companies, the influence of size, leverage, and profitability on FERC, and market response. Thus, this study will provide an in-depth understanding of how these factors are interrelated and impact market reactions to future earnings, with tax compliance as an important moderating factor. This study aims to analyze the influence of market power and systematic risk on the future earnings response coefficient (ERC), with tax compliance as a moderating factor. In this context, the study will examine how market power and systematic risk affect market reactions to future earnings, considering the role of tax compliance as a moderating factor. Relevant references for this study include factor analysis that influences ERC in financial sector companies, the influence of size, leverage, and profitability on FERC, and market response. Thus, this study will provide an in-depth understanding of how these factors are interrelated and impact market reactions to future earnings, with tax compliance as an important moderating factor.